THE LOST INDIAN CHANDRAYAAN 2 LANDER VIKRAM AND ROVER PRAGYAAN FOUND INTACT IN SINGLE PIECE ON THE MOON - Saxena, Jag Mohan; Saxena, H M; Saxena, Priyanka (International Journal of Research -GRANTHAALAYAH, 2020)
The Lunar Lander Vikram of the Moon Mission Chandrayaan 2 of the Indian Space Research Organization (ISRO) lost communication with the Lunar Orbiter and the mission control nearly 2.1 kms above the lunar surface during its landing on the Moon on 7th September, 2019. The exact location and the sight of the lost lander and rover are still elusive. We present here the exact location and first images of the lander Vikram and rover Pragyaan sighted on the lunar surface. It is evident from the processed images that the lander was intact and in single piece on landing away from the scheduled site and its ramp was deployed to successfully release the rover Pragyan on to the lunar surface. This contradicts earlier reports that the lander was disintegrated into small pieces and debris which were scattered far away from the proposed landing site.